PP.24.16: PERIPHERAL, CENTRAL NON INVASIVE HEMODYNAMICS AND ARTERIAL SITFFNESS IN EARLY PUERPERIUM NORMAL AND COMPLICATED HYPERTENSIVE DISEASE PREGNANCY. (June 2015) - Lopez-Rivera, J.; Cedeño-Buitrago, M.; Lopez-Saavedra, J.; Scrocchi, S.; Badillo, M.
Abstract : Objective: Hypertensive disorders of pregnancy are the most common medical complication, increase maternal / fetal morbidity and mortality, with prevalence from 5% to 20% depending on the revised series and are characterized by poor maternal cardiovascular adaptation to pregnancy, where the pathophysiological background lies in a severe systemic endothelial dysfunction. The aim of this study was to compare the changes in arterial elasticity, by assessing peripheral and central noninvasive hemodynamics, and arterial stiffness index, in a normal and hypertensive disease that had complicated pregnancy in early puerperium. Figure. No caption available. Design and method: Observational, cross-sectional study in 102 early puerperal women in obstetrics service, during the month of November and December 2014, it was determined the values of hemodynamics peripheral and central, no invasive, and evaluation arterial stiffness index with recorder Mobil -O- graph PWV, IEM, descriptive statistical analysis of parametric variables was performed, and the resulting values of hemodynamics and arterial stiffness between normal and those with hypertensive disease of pregnancy in early puerperium were compared to determine if was statistically significant difference among them; SPS 19 software was used and evaluated using T student with a confidence level of 95%. Results: Of the 102 enrolled, 76 were normal pregnancy and 26 were hypertensive disease of pregnancy, these all were receiving antihypertensive treatment, 17 had preeclampsia, eclampsia 3 and 6 were chronic hypertension. The average age was 22.2 years with ED: 6. 37, 25 gestational weeks, with an average of 12 hours postpartum. Statistically significant difference was observed with a P < 0.05 between brachial systolic pressure, central systolic pressure, central pulse pressure, pulse wave velocity, and augmentation pressure, not in others, among the group with hypertensive disease pregnancy and normal pregnancy. Conclusions: Early puerperium patients with hypertensive disease of pregnancy occurring with impaired arterial elasticity, these findings open an interesting field in the evaluation and treatment of this pathology.